2011
DOI: 10.1111/j.1469-8137.2011.03916.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of function for conserved noncoding sequences in Arabidopsis thaliana

Abstract: Summary• Whole genome duplication events provide a lineage with a large reservoir of genes that can be molded by evolutionary forces into phenotypes that fit alternative environments. A well-studied whole genome duplication, the a-event, occurred in an ancestor of the model plant Arabidopsis thaliana. Retained segments of the a-event have been defined in recent years in the form of duplicate protein coding sequences (a-pairs) and associated conserved noncoding DNA sequences (CNSs). Our aim was to identify any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…The Klein lab characterized changes in the expression of sorghum seedling shoots and seedling roots in response to the hormone ABA and simulated osmotic stress produced by the application of polyethylene glycol (Dugas et al, 2011). Using the RNA-Seq reads generated in that set of experiments we found that genes with many CNS tended to have globally lower expression levels regardless of environmental conditions (Figure 4), consistent with a previous microarray-based study of the link between conserved promoter complexity and gene expression in arabidopsis (Spangler et al, 2012). Genes with few CNS were equally likely to show up or down regulation when sorghum seedlings where exposed to ABA or osmotic stress.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The Klein lab characterized changes in the expression of sorghum seedling shoots and seedling roots in response to the hormone ABA and simulated osmotic stress produced by the application of polyethylene glycol (Dugas et al, 2011). Using the RNA-Seq reads generated in that set of experiments we found that genes with many CNS tended to have globally lower expression levels regardless of environmental conditions (Figure 4), consistent with a previous microarray-based study of the link between conserved promoter complexity and gene expression in arabidopsis (Spangler et al, 2012). Genes with few CNS were equally likely to show up or down regulation when sorghum seedlings where exposed to ABA or osmotic stress.…”
Section: Resultssupporting
confidence: 88%
“…Recent work in rice has shown a postive correlation between open chromatin and CNSs (Zhang et al, 2012). Arabidopsis homeologs with many associated five prime CNS tend to show less expression than arabidopsis genes with fewer CNS (Spangler et al, 2012). There is also evidence that genes with the most associated CNS (CNS-richness) are more likely to be retained following whole genome duplication, perhaps because of selection against disruption of DNA-protein stoichiometries (Schnable et al, 2011) or perhaps because they are more readily subfunctionalized (Force et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative methods using metrics other than sequence alignments (such as the alignment-free model of Koohy et al, 2010) are needed to find the subset of regulatory elements that are functionally but not alignment conserved. Methods that combine comparative genomics with other resources, such as gene expression (as in Vandepoele et al, 2006;Heyndrickx and Vandepoele, 2012;Spangler et al, 2012), are also useful in aiding the discovery and analysis of regulatory modules.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression data generated from the Affymetrix Arabidopsis ATH1 Genome Array (GPL198) were obtained from previous studies [26,49]. The expression divergence between duplicated genes was measured by 1- r , where r is the Pearson’s correlation coefficient between their expression profiles [26].…”
Section: Methodsmentioning
confidence: 99%